Hubungan Pengetahuan Berbusana Dengan Penampilan Diri Mahasiswa Jurusan Pendidikan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Manado - Rini Kusma Safitri; Henny Jeane Polii; Louisa Nicolina Kandoli (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study explores the self-appearance of Fashion Design students in the Family Welfare Education Department, Faculty of Engineering, Manado State University. The aim of the research is to examine the relationship between fashion knowledge and the self-appearance of these students. This is a descriptive correlational study, which provides an overview of the relationship between the variable of fashion knowledge (X) and the variable of self-appearance (Y). The population in this study consists of 50 undergraduate Fashion Design students from the 2021–2024 cohorts, with a sample size of 33 students. The sample was selected using a simple random sampling technique. The research instrument used was a questionnaire based on a Likert scale. Data analysis techniques included descriptive statistics, data quality testing, and a t-test. The results of the study reveal that there is a positive relationship between fashion knowledge and the self-appearance of Fashion Design students in the Family Welfare Education Department, Faculty of Engineering, Manado State University, with a contribution of 51.3%.